Trial of Immune Globulin in Infant Botulism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
A 5-year, randomized, double-blind, placebo-controlled trial of the orphan drug Human Botulism Immune Globulin Intravenous (BIG-IV) in 122 infants in California with confirmed infant botulism (75 caused by type A Clostridium botulinum toxin, and 47 by type B toxin) was conducted at the California Department of Health Services, Richmond, CA; National Botulism Surveillance and Reference Laboratory, CDC and P, Atlanta; and Division of Biostatistics, University of California, Berkeley.